2020
DOI: 10.3390/ijerph17228576
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Pedestrian’s Perceptions of Safety on Street Crossings. Psychological and Neurophysiological Effects of Traffic Lanes, Artificial Lighting, and Vegetation

Abstract: The effect that the physical characteristics of urban design have on the pedestrian’s perceptions of safety is a fundamental aspect of city planning. This is particularly so with street crossings, where the pedestrian has to make a decision. This paper analyses how pedestrians are affected by number of traffic lanes, lighting colour temperature, and nearby vegetation as they cross roads. Perceptions of safety were quantified by means of the psychological and neurophysiological responses of 60 participants to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…People felt more stressed in spaces with more crowded pedestrian areas and at the intersection of traffic lanes (bicycles, cars). This finding is somewhat similar to the finding of Llinares et al [ 18 ] indicating that a higher number of traffic lanes leads to a lower perception of safety. With regard to cycling, they found that a wider bicycle lane leads to less stress compared to a narrow bicycle lane.…”
Section: Types Of Public Spacesupporting
confidence: 92%
See 3 more Smart Citations
“…People felt more stressed in spaces with more crowded pedestrian areas and at the intersection of traffic lanes (bicycles, cars). This finding is somewhat similar to the finding of Llinares et al [ 18 ] indicating that a higher number of traffic lanes leads to a lower perception of safety. With regard to cycling, they found that a wider bicycle lane leads to less stress compared to a narrow bicycle lane.…”
Section: Types Of Public Spacesupporting
confidence: 92%
“…In a pilot study, a walking simulator with a locomotive technology was combined with bio-sensing data, eye tracking and gait sensor data. Moreover, Llinares et al [ 18 ] and Krzywicka and Byrka [ 17 ] also made use of virtual urbanscapes and soundscapes on the assessment of surroundings. These studies on virtual environments add another dimension to urban design and well-being, especially for capturing how citizens will experience and perceive new (upcoming) urban design interventions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, to investigate perceived safety in PPS, a visual assessment survey was conducted using recorded virtual reality (VR) videos. Recent studies using VR have dealt with perception and cognition related to the urban environments [ 11 , 12 , 13 , 14 ], and VR has been widely acknowledged as a research instrument [ 15 , 16 , 17 ]. In particular, VR could be used as a means to investigate the risk perception of pedestrians.…”
Section: Introductionmentioning
confidence: 99%